PENERAPAN PEMBELAJARAN KALIGRAFI DALAM MENULIS AL-QUR’AN: SEBUAH TINJAUAN LITERATUR - Lijar Pastilah; Aulia Pratama Putra (CV. Adiba Aisha Amira, 2025)
This study discusses the application of calligraphy learning in writing the Qur'an and its impact on students' skills. Calligraphy as the art of writing has an important role in Islamic tradition, not only as a writing technique but also as a spiritual and cultural expression. Through the literature study method, this study explores various approaches that have been applied and the challenges faced in learning calligraphy. The results of the study indicate that calligraphy learning improves the ability to write the Qur'an by 54.05%, reading and writing skills by 18.92%, creativity by 8.11%, and maharah al-kitabah by 10.81%. In addition, this learning also helps memorize the Qur'an and increases motivation to learn Islam. Although there are challenges, such as lack of student interest (50%), difficulty in writing (33%), and time constraints (17%), an innovative approach can help overcome these problems. This study is expected to make a significant contribution to the development of curriculum and teaching methods in Islamic educational institutions.